Progress claim / Muhammad Fareez Razzey Rusli - Rusli, Muhammad Fareez Razzey (2016)
Progress claim is a very important thing in any construction, therefore this report will discuss about progress claim for main-contractor. This report is conducted based on experiences and knowledge gained during the industrial training at Bluebros E&C Sdn Bhd in Genting Highland. The objective of this report is to explain in detail about progress claim. It will focus on sequences of works in preparation of progress claim, parties and documents involved in progress claim works. In addition, this report will also look at the problems occur during the preparation of progress claim and on how to overcome the problems occured. The proposed tittle is being done by collecting data and informations with aid of technology which is internet, books, interview and observation. In order to complete this report, it is needed to make observation along the way in the industrial training and as a theoritical support, books, website and meeting knowledgeable person are important.